Environment-friendly flame-retardant pearl wool and preparation method thereof
By adding antistatic masterbatches to pearl cotton and using thermally expanded microspheres for foaming, the problem of insufficient antistatic performance of pearl cotton is solved, and the effect of improving antistatic performance and mechanical strength is achieved, and the demand for electronic equipment packaging materials is met.
Patent Information
- Application Number
- CN202411916423.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing pearl cotton has problems with insufficient antistatic performance in electronic equipment packaging materials, resulting in degradation of electronic equipment performance or damage to sensitive electronic components.
Environmentally friendly flame-retardant pearl cotton is prepared by adding antistatic masterbatches, such as carbon nanotubes and carbon fibers, and mixing them with EVA elastomer and maleic anhydride grafted polyethylene compatible agent, and foaming in combination with thermally expanded microspheres.
It improves the antistatic properties of pearl cotton, enhances its mechanical strength and flame retardant properties, and meets the needs of electronic equipment packaging materials.
Smart Images

Figure BDA0005206921690000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flame-retardant pearl cotton, and particularly relates to an environmentally friendly flame-retardant pearl cotton and a preparation method thereof. Background Art
[0002] Pearl cotton is the common name for polyethylene foam. It is composed of countless independent bubbles produced by physical foaming of low-density polyethylene resin. It has high elasticity and its bubble structure makes it soft and light. It not only saves materials and costs, but also overcomes the shortcomings of ordinary foam rubber, such as fragility, deformation, and poor recovery. Pearl cotton is non-toxic and harmless, has the advantages of moisture-proof, shock-proof, and strong cushioning performance. It can be recycled repeatedly and will not pollute the environment. It is widely used as packaging materials.
[0003] Pearl cotton is generally prepared by physical foaming. Before the polymer is foamed and molded, a physical foaming agent is added to it by pressure. When heated, the physical foaming agent is vaporized to foam the polymer. Physical foaming agents mostly use inert gases, such as air, nitrogen and carbon dioxide. High pressure and sealing need to be maintained during the foaming process. The main disadvantage is the high equipment investment. Another physical foaming method is to foam by heat-expandable microspheres, such as the commercially available Expansion l microspheres. Heat-expandable microspheres have a complete spherical structure and a closed-cell structure. After foaming, the volume expansion multiple is high, the pores are uniform, the mechanical properties are good, the resilience is good, and it can withstand multiple cycles of pressurization / decompression without breaking. Compared with the foaming form using inert gases, it can inhibit the occurrence of surface degradation.
[0004] With the widespread demand for electronic devices in life, safe logistics and transportation of electronic products has become particularly critical during the purchase and sale of electronic products. In addition to the need for flame retardancy and fire protection, polymer foams are also prone to static electricity accumulation, which may cause performance degradation of electronic devices or damage sensitive electronic components. Therefore, how to improve the antistatic properties of pearl cotton foaming has become a research focus of electronic equipment packaging materials. Summary of the invention
[0005] The purpose of the present invention is to provide an environmentally friendly flame-retardant pearl cotton and a preparation method thereof, and to improve the antistatic performance of the pearl cotton by adding antistatic masterbatch as a raw material, thereby meeting the use requirements of electronic equipment packaging materials.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for preparing environmentally friendly flame-retardant pearl cotton comprises the following steps:
[0008] Add low-density polyethylene resin, antistatic masterbatch, antioxidant and stearic acid into a high-speed mixer and mix evenly, then add flame-retardant heat-expandable microspheres and mix evenly again to obtain a mixture, transfer the mixture to an extrusion foaming machine for extrusion foaming, the extrusion temperature is 130-140°C, the foaming temperature is 175-190°C, the foaming time is 6-7min, naturally cool, cut and shape to obtain environmentally friendly flame-retardant pearl cotton.
[0009] The mass ratio of low-density polyethylene resin, antistatic masterbatch, antioxidant, stearic acid and flame-retardant thermal expansion microspheres is 80-85:20-22:1:1:6.5-7.
[0010] Further, the antistatic masterbatch is prepared by the following steps:
[0011] Add carbon nanotubes, carbon fibers and dimethylformamide into a reactor, perform ultrasonic dispersion for 3-4 hours, then add EVA elastomer and maleic anhydride grafted polyethylene compatibilizer into the reactor, stir for 1.5-2 hours at 50-60°C and 300-500r / min, concentrate under reduced pressure to recover dimethylformamide, vacuum dry the remaining solid, crush and pelletize to obtain antistatic masterbatch.
[0012] Furthermore, the usage ratio of carbon nanotubes, carbon fibers, dimethylformamide, EVA elastomer and maleic anhydride grafted polyethylene compatibilizer is 2-3:4-6:1000-1500:50-80:50-60.
[0013] Furthermore, the flame retardant heat-expandable microspheres are prepared by the following steps:
[0014] Step 1: Add heat-expandable microspheres and a hydroxylamine aqueous solution with a molar concentration of 1 mol / L into a reactor at a mass ratio of 1:400-500, stir for 10-15 minutes at 60-70°C and 200-300r / min, filter, wash the filter cake with deionized water 2-3 times, and vacuum dry at 45-50°C to obtain modified heat-expandable microspheres.
[0015] Step 2: Add aluminum nitrate nonahydrate and anhydrous ethanol to a reactor, stir at 20-25° C. and 200-300 r / min for 10-15 min, then add modified heat-expandable microspheres to the reactor, ultrasonically disperse for 10-15 min, then add 1.75% 2-methylimidazole ethanol solution to the reactor, continue stirring for 60-80 min, then stand at 35° C. for 24 h, centrifuge and filter, wash the filter cake with anhydrous ethanol for 2-3 times, and vacuum dry at 45-50° C. to obtain composite heat-expandable microspheres.
[0016] Step 3: Add 3-phenylsulfonylbenzenesulfonic acid flame retardant powder and deionized water into the reactor, stir at 20-25°C and 200-300r / min for 10-15min, then add the composite thermal expansion microspheres into the reactor, ultrasonically disperse for 8-12h, filter, wash the filter cake with deionized water for 2-3 times, and vacuum dry at 45-50°C to obtain flame retardant thermal expansion microspheres.
[0017] Furthermore, the dosage ratio of aluminum nitrate nonahydrate, anhydrous ethanol, modified heat-expandable microspheres and methanol solution of 2-methylimidazole is 0.25-0.3 g: 30 mL: 0.1-0.12 g: 30 mL.
[0018] Furthermore, the mass ratio of 3-phenylsulfonylbenzenesulfonic acid flame retardant powder, deionized water and composite thermal expansion microspheres is 1:100:2-2.5.
[0019] Further, the heat-expandable microspheres are prepared by the following steps:
[0020] (1) adding magnesium chloride hexahydrate, sodium dodecyl sulfate and deionized water into a reaction kettle, stirring at a speed of 800-1000 r / min for 20-30 min, then adding sodium nitrite and polyvinyl pyrrolidone into the reaction kettle, and ultrasonically dispersing for 15-20 min to obtain an aqueous phase;
[0021] Furthermore, the mass ratio of magnesium chloride hexahydrate, sodium dodecyl sulfate, deionized water, sodium nitrite and polyvinyl pyrrolidone is 10-12: 1-1.5: 95-105: 0.02-0.03: 0.02-0.03.
[0022] (2) dissolving ethylene glycol dimethacrylate, azobisisobutyronitrile and a foaming agent in a polymerizable monomer to obtain an oil phase, which is stored at 0-4°C;
[0023] Furthermore, the mass ratio of ethylene glycol dimethacrylate, azobisisobutyronitrile, foaming agent and polymerizable monomer is 0.24-0.26:1.2-1.5:24-26:95-100.
[0024] (3) Add the aqueous phase to a homogenizer, add the oil phase to the homogenizer under stirring conditions of 8000-10000 r / min, transfer the obtained emulsion to a reactor after stirring for 2-3 minutes, heat to 60°C under nitrogen protection and 300-500 r / min, keep the temperature for reaction for 20-24 hours, and then stand and mature at 70°C for 20-30 minutes, adjust the pH value to 2 with hydrochloric acid with a molar concentration of 0.1 mol / L, filter, wash the filter cake with deionized water until the last washing liquid is neutral, and vacuum dry at 45-50°C to obtain heat-expandable microspheres.
[0025] Furthermore, the mass ratio of the water phase to the oil phase is 1.2:1.
[0026] Furthermore, the blowing agent is any one of isobutane, n-pentane and isopentane.
[0027] Furthermore, the polymerizable monomer is prepared by mixing methyl methacrylate, N,N-dimethylacrylamide and vinyl acetate in a mass ratio of 7:3:1.
[0028] Further, 3-phenylsulfonylbenzenesulfonic acid flame retardant powder is prepared by the following steps:
[0029] Potassium 3-phenylsulfonylbenzenesulfonate and a hydrochloric acid solution with a molar concentration of 0.1 mol / L are added into a reaction kettle in a mass ratio of 1:20-25, stirred for 10-12 hours under the conditions of ultrasonic assistance, 30-35° C. and 500-800 r / min, and centrifuged and washed 3-5 times to obtain 3-phenylsulfonylbenzenesulfonic acid flame retardant powder.
[0030] Furthermore, the power of ultrasonic assistance is 450-500W and the frequency is 30-40KHz.
[0031] Beneficial effects of the present invention:
[0032] 1. The environmentally friendly flame-retardant pearl cotton of the present invention is foamed by heat-expandable microspheres, has good mechanical strength, is environmentally friendly and pollution-free, and carbon nanotubes and carbon fibers are dispersed as conductive agents through dimethylformamide, and then mixed with dissolved EVA elastomer and maleic anhydride grafted polyethylene compatibilizer, which helps to disperse them evenly in the polymer, reduce the surface impedance of the pearl cotton, and thus improve the antistatic effect of the pearl cotton. Carbon nanotubes and carbon fibers can also play a reinforcing role in the environmentally friendly flame-retardant pearl cotton, meeting the use requirements of electronic equipment packaging materials.
[0033] 2. The flame-retardant heat-expandable microspheres of the present invention have a high heat expansion temperature and meet the foaming requirements of polyethylene pearl cotton. The modified heat-expandable microspheres are obtained by modification with hydroxylamine, which can react with the cyano group on the surface of the heat-expandable microspheres to generate amide oxime groups, which have high affinity for metal ions; the amide oxime groups chelate the aluminum ions in the reaction solution, and then 2-methylimidazole is used as a ligand to assemble aluminum ions to form a metal organic framework, and a layer of coating particles is loaded on the surface of the modified heat-expandable microspheres; the coating particles have a porous structure, which helps to absorb more 3-phenylsulfonylbenzenesulfonic acid flame retardant, and the aluminum ions therein can react with the sulfonic acid groups in the 3-phenylsulfonylbenzenesulfonic acid flame retardant to increase the load stability, and solve the problem of directly adding 3-phenylsulfonylbenzenesulfonic acid potassium as a flame retardant, which has poor dispersibility and leads to a decrease in flame retardant effect. DETAILED DESCRIPTION
[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Embodiment 1: This embodiment provides an environmentally friendly flame-retardant pearl cotton, which is prepared by the following method:
[0036] S1: 2kg carbon nanotubes, 4kg carbon fibers and 1000kg dimethylformamide were added to a reactor, ultrasonically dispersed for 3h, and then 50kg EVA elastomer and 50kg maleic anhydride grafted polyethylene compatibilizer were added to the reactor, stirred at 50°C and 300r / min for 1.5h, concentrated under reduced pressure to recover dimethylformamide, and the remaining solid was vacuum dried, crushed and pelletized to obtain an antistatic masterbatch.
[0037] Carbon nanotubes and carbon fibers as conductive agents were dispersed by dimethylformamide and then mixed with dissolved EVA elastomer and maleic anhydride grafted polyethylene compatibilizer to help them disperse evenly in the polymer.
[0038] S2: 10 kg of magnesium chloride hexahydrate, 1 kg of sodium dodecyl sulfate and 95 kg of deionized water were added to a reactor, stirred at a speed of 800 r / min for 20 min, and then 0.02 kg of sodium nitrite and 0.02 kg of polyvinyl pyrrolidone were added to the reactor, and ultrasonic dispersion was performed for 15 min to obtain an aqueous phase;
[0039] Methyl methacrylate, N,N-dimethylacrylamide and vinyl acetate were mixed in a mass ratio of 7:3:1 to obtain a polymerizable monomer, 0.24 kg of ethylene glycol dimethacrylate, 1.2 kg of azobisisobutyronitrile and 24 kg of isobutane were dissolved in 95 kg of the polymerizable monomer to obtain an oil phase, which was stored at 0°C;
[0040] 12 kg of water phase was added to a homogenizer, and 10 kg of oil phase was added to the homogenizer under stirring conditions of 8000 r / min. After stirring for 2 minutes, the obtained emulsion was transferred to a reactor, and the temperature was raised to 60°C under nitrogen protection and 300 r / min. The reaction was kept warm for 20 hours, and then allowed to stand and mature at 70°C for 20 minutes. The pH value was adjusted to 2 with hydrochloric acid with a molar concentration of 0.1 mol / L, and the filter cake was washed with deionized water until the last washing liquid was neutral, and then vacuum dried at 45°C to obtain heat-expandable microspheres.
[0041] S3: Heat-expandable microspheres and a hydroxylamine aqueous solution with a molar concentration of 1 mol / L were added into a reactor in a mass ratio of 1:400, stirred at 60°C and 200 r / min for 10 min, filtered, the filter cake was washed twice with deionized water, and vacuum dried at 45°C to obtain modified heat-expandable microspheres.
[0042] Hydroxylamine can react with the cyano group on the surface of the heat-expandable microspheres to generate amide oxime groups, which have a high affinity for metal ions.
[0043] S4: Add 2.5 kg of aluminum nitrate nonahydrate and 300 L of anhydrous ethanol into a reactor, stir at 20°C and 200 r / min for 10 min, then add 1 kg of modified heat-expandable microspheres into the reactor, ultrasonically disperse for 10 min, then add 300 L of ethanol solution of 2-methylimidazole with a mass concentration of 1.75% into the reactor, continue stirring for 60 min, then let stand at 35°C for 24 h, centrifuge and wash the filter cake twice with anhydrous ethanol, and vacuum dry at 45°C to obtain composite heat-expandable microspheres.
[0044] The amide oxime groups on the surface of the modified heat-expandable microspheres chelate aluminum ions in the reaction solution, and then 2-methylimidazole is used as a ligand to assemble aluminum ions to form a metal organic framework, and a layer of coating particles is loaded on the surface of the modified heat-expandable microspheres.
[0045] S5: Potassium 3-phenylsulfonylbenzenesulfonate and a hydrochloric acid solution with a molar concentration of 0.1 mol / L are added into a reactor in a mass ratio of 1:20-25, stirred for 10 hours under the conditions of ultrasonic assistance, 30°C and 500 r / min, and centrifuged and washed 3 times to obtain 3-phenylsulfonylbenzenesulfonic acid flame retardant powder; wherein the power of ultrasonic assistance is 450 W and the frequency is 30 KHz.
[0046] S6: 100 kg of 3-phenylsulfonylbenzenesulfonic acid flame retardant powder and 10 kg of deionized water were added to the reactor, stirred at 20°C and 200 r / min for 10 min, and then 200 g of composite heat-expandable microspheres were added to the reactor, ultrasonically dispersed for 8 h, filtered, and the filter cake was washed twice with deionized water and vacuum dried at 45°C to obtain flame-retardant heat-expandable microspheres.
[0047] The coating layer particles on the surface of the composite thermal expansion microspheres have a porous structure, which is helpful to absorb more 3-phenylsulfonylbenzenesulfonic acid flame retardant, and the aluminum ions therein can react with the sulfonic acid groups in the 3-phenylsulfonylbenzenesulfonic acid flame retardant to increase the loading stability.
[0048] S7: Add 800g of low-density polyethylene resin, 200g of antistatic masterbatch, 10g of antioxidant 1010 and 10g of stearic acid into a high-speed mixer and mix evenly, then add 65g of flame-retardant heat-expandable microspheres and mix evenly again to obtain a mixture, transfer the mixture to an extrusion foaming machine for extrusion foaming, the extrusion temperature is 130°C, the foaming temperature is 175°C, the foaming time is 6min, naturally cool, cut into shape, and obtain environmentally friendly flame-retardant pearl cotton.
[0049] Embodiment 2: This embodiment provides an environmentally friendly flame-retardant pearl cotton, which is prepared by the following method:
[0050] S1: 2.5 kg carbon nanotubes, 5 kg carbon fibers and 1250 kg dimethylformamide were added to a reactor, and ultrasonic dispersion was performed for 3.5 h. Then, 65 kg EVA elastomer and 55 kg maleic anhydride grafted polyethylene compatibilizer were added to the reactor, and stirred at 55 ° C and 400 r / min for 1.8 h. The dimethylformamide was recovered by vacuum concentration, and the remaining solid was vacuum dried, crushed and pelletized to obtain an antistatic masterbatch.
[0051] S2: 11 kg of magnesium chloride hexahydrate, 1.2 kg of sodium dodecyl sulfate and 100 kg of deionized water were added to a reactor, stirred at a speed of 900 r / min for 25 min, and then 0.025 kg of sodium nitrite and 0.025 kg of polyvinyl pyrrolidone were added to the reactor, and ultrasonic dispersion was performed for 18 min to obtain an aqueous phase;
[0052] Methyl methacrylate, N,N-dimethylacrylamide and vinyl acetate are mixed in a mass ratio of 7:3:1 to obtain a polymerizable monomer, 0.25 kg of ethylene glycol dimethacrylate, 1.35 kg of azobisisobutyronitrile and 25 kg of n-pentane are dissolved in 98 kg of the polymerizable monomer to obtain an oil phase, which is stored at 0-4°C;
[0053] 12 kg of water phase was added to a homogenizer, and 10 kg of oil phase was added to the homogenizer under stirring conditions of 9000 r / min. After stirring for 2.5 min, the obtained emulsion was transferred to a reactor, and the temperature was raised to 60°C under nitrogen protection and 400 r / min. The reaction was kept warm for 22 h, and then allowed to stand and mature at 70°C for 25 min. The pH value was adjusted to 2 with hydrochloric acid having a molar concentration of 0.1 mol / L, and the filter cake was washed with deionized water until the last washing liquid was neutral, and then dried in vacuo at 48°C to obtain heat-expandable microspheres.
[0054] S3: Heat-expandable microspheres and a hydroxylamine aqueous solution with a molar concentration of 1 mol / L were added into a reactor in a mass ratio of 1:400-500, stirred at 65°C and 250 r / min for 12 min, filtered, washed the filter cake twice with deionized water, and dried in vacuo at 48°C to obtain modified heat-expandable microspheres.
[0055] S4: Add 2.8 kg of aluminum nitrate nonahydrate and 300 L of anhydrous ethanol into a reactor, stir at 22°C and 250 r / min for 12 min, then add 1.1 kg of modified heat-expandable microspheres into the reactor, ultrasonically disperse for 10-15 min, then add 300 L of ethanol solution of 2-methylimidazole with a mass concentration of 1.75% into the reactor, continue stirring for 70 min, then let stand at 35°C for 24 h, centrifuge and wash the filter cake twice with anhydrous ethanol, and vacuum dry at 48°C to obtain composite heat-expandable microspheres.
[0056] S5: Potassium 3-phenylsulfonylbenzenesulfonate and a hydrochloric acid solution with a molar concentration of 0.1 mol / L were added into a reactor in a mass ratio of 1:22, stirred for 11 hours under the conditions of ultrasonic assistance, 32°C and 650 r / min, and centrifuged and washed 4 times to obtain 3-phenylsulfonylbenzenesulfonic acid flame retardant powder; wherein the power of ultrasonic assistance was 480 W and the frequency was 35 KHz.
[0057] S6: 100 kg of 3-phenylsulfonylbenzenesulfonic acid flame retardant powder and 10 kg of deionized water were added to the reactor, stirred at 22°C and 250 r / min for 12 min, and then 225 g of composite heat-expandable microspheres were added to the reactor, ultrasonically dispersed for 10 h, filtered, and the filter cake was washed twice with deionized water and vacuum dried at 48°C to obtain flame-retardant heat-expandable microspheres.
[0058] S7: Add 825g of low-density polyethylene resin, 210g of antistatic masterbatch, 10g of antioxidant 1010 and 10g of stearic acid into a high-speed mixer and mix evenly, then add 68g of flame-retardant heat-expandable microspheres and mix evenly again to obtain a mixture, transfer the mixture to an extrusion foaming machine for extrusion foaming, the extrusion temperature is 135°C, the foaming temperature is 180°C, the foaming time is 6.5min, cool naturally, cut into shape, and obtain environmentally friendly flame-retardant pearl cotton.
[0059] Embodiment 3: This embodiment provides an environmentally friendly flame-retardant pearl cotton, which is prepared by the following method:
[0060] S1: 3kg carbon nanotubes, 6kg carbon fibers and 1500kg dimethylformamide were added to a reactor, ultrasonically dispersed for 4h, and then 80kg EVA elastomer and 60kg maleic anhydride grafted polyethylene compatibilizer were added to the reactor, stirred at 60°C and 500r / min for 2h, concentrated under reduced pressure to recover dimethylformamide, and the remaining solid was vacuum dried, crushed and pelletized to obtain antistatic masterbatch.
[0061] S2: 12 kg of magnesium chloride hexahydrate, 1.5 kg of sodium dodecyl sulfate and 105 kg of deionized water were added to a reactor, stirred at a speed of 1000 r / min for 30 min, and then 0.03 kg of sodium nitrite and 0.03 kg of polyvinyl pyrrolidone were added to the reactor, and ultrasonically dispersed for 20 min to obtain an aqueous phase;
[0062] Methyl methacrylate, N,N-dimethylacrylamide and vinyl acetate were mixed in a mass ratio of 7:3:1 to obtain a polymerizable monomer, 0.26 kg of ethylene glycol dimethacrylate, 1.5 kg of azobisisobutyronitrile and 26 kg of isopentane were dissolved in 100 kg of the polymerizable monomer to obtain an oil phase, which was stored at 4°C;
[0063] 12 kg of water phase was added to a homogenizer, and 10 kg of oil phase was added to the homogenizer under stirring conditions of 10000 r / min. After stirring for 3 minutes, the obtained emulsion was transferred to a reactor, and the temperature was raised to 60°C under nitrogen protection and 500 r / min. The reaction was kept warm for 24 hours, and then allowed to stand and mature at 70°C for 30 minutes. The pH value was adjusted to 2 with hydrochloric acid with a molar concentration of 0.1 mol / L, and the filter cake was washed with deionized water until the last washing liquid was neutral, and then vacuum dried at 50°C to obtain heat-expandable microspheres.
[0064] S3: Heat-expandable microspheres and a hydroxylamine aqueous solution with a molar concentration of 1 mol / L were added into a reactor in a mass ratio of 1:500, stirred at 70°C and 300 r / min for 15 min, filtered, the filter cake was washed with deionized water for 3 times, and vacuum dried at 50°C to obtain modified heat-expandable microspheres.
[0065] S4: 3 kg of aluminum nitrate nonahydrate and 300 L of anhydrous ethanol were added to a reactor, stirred at 25°C and 300 r / min for 15 min, then 1.2 kg of modified heat-expandable microspheres were added to the reactor, ultrasonically dispersed for 15 min, and then 300 L of 2-methylimidazole ethanol solution with a mass concentration of 1.75% was added to the reactor, and stirring was continued for 80 min, and then allowed to stand at 35°C for 24 h, centrifuged and filtered, the filter cake was washed 3 times with anhydrous ethanol, and vacuum dried at 50°C to obtain composite heat-expandable microspheres.
[0066] S5: Potassium 3-phenylsulfonylbenzenesulfonate and a hydrochloric acid solution with a molar concentration of 0.1 mol / L are added into a reactor in a mass ratio of 1:25, stirred for 12 hours at 35°C and 800 r / min under ultrasonic assistance, and centrifuged and washed 5 times to obtain 3-phenylsulfonylbenzenesulfonic acid flame retardant powder; wherein the power of ultrasonic assistance is 500 W and the frequency is 40 KHz.
[0067] S6: 100 kg of 3-phenylsulfonylbenzenesulfonic acid flame retardant powder and 10 kg of deionized water were added to the reactor, stirred at 25°C and 300 r / min for 15 min, and then 250 g of composite heat-expandable microspheres were added to the reactor, ultrasonically dispersed for 12 h, filtered, and the filter cake was washed with deionized water for 3 times, and vacuum dried at 50°C to obtain flame-retardant heat-expandable microspheres.
[0068] S7: Add 850g of low-density polyethylene resin, 220g of antistatic masterbatch, 10g of antioxidant 1010 and 10g of stearic acid into a high-speed mixer and mix evenly, then add 70g of flame-retardant heat-expandable microspheres and mix evenly again to obtain a mixture, transfer the mixture to an extrusion foaming machine for extrusion foaming, the extrusion temperature is 140°C, the foaming temperature is 190°C, the foaming time is 7min, naturally cool, cut into shape, and obtain environmentally friendly flame-retardant pearl cotton.
[0069] Comparative Example 1: Based on Example 3, no antistatic masterbatch was added, and the other steps remained unchanged to prepare pearl cotton.
[0070] Comparative Example 2: Based on Example 3, the heat-expandable microspheres in step S2 are directly processed according to step S4 and subsequent steps without being processed in step S3, and the remaining steps remain unchanged to prepare pearl cotton.
[0071] Comparative Example 3: On the basis of Example 3, without the treatment in steps S4 to S6, the modified heat-expandable microspheres in step S3 and potassium 3-benzenesulfonylbenzenesulfonate are directly mixed in a mass ratio of 2.5:1, and the flame-retardant heat-expandable microspheres in step S7 are replaced. The other steps remain unchanged to prepare pearl cotton.
[0072] Comparative Example 4: On the basis of Example 3, without the treatment in step S6, the composite heat-expandable microspheres and potassium 3-benzenesulfonylbenzenesulfonate in step S4 are directly mixed in a mass ratio of 2.5:1, and the flame-retardant heat-expandable microspheres in step S7 are replaced. The other steps remain unchanged to prepare pearl cotton.
[0073] The carbon nanotubes and carbon fibers in the examples and comparative examples were purchased from Sigma-Aldrich.
[0074] Performance tests were performed on Examples 1 to 3 and Comparative Examples 1 to 4. Samples were prepared according to the corresponding test standards. The surface impedance of different samples was tested using a surface resistivity meter according to ASTM-D257. The tensile strength and elongation at break of different samples were tested according to GB / T 6344-2008. The oxygen index was determined according to GB / T 2406-2008. The results are shown in Table 1.
[0075] Table 1 Results of each pearl cotton performance index
[0076]
[0077] It can be seen from Table 1 that the surface impedance of the environmentally friendly flame-retardant pearl cotton in Examples 1 to 3 is low, indicating that it has a good antistatic effect and has high mechanical properties and oxygen index.
[0078] No antistatic masterbatch was added to Comparative Example 1, and its tensile strength and elongation at break also decreased because the carbon nanotubes and carbon fibers therein also have a reinforcing effect; the flame retardant effects of Comparative Examples 3-4 are poor, which may be due to the poor dispersibility of directly added potassium 3-phenylsulfonylbenzenesulfonate, resulting in agglomeration and the like, which leads to a decrease in the flame retardant effect; the flame retardant effect in Comparative Example 2 is reduced, which may be because the surface of the heat-expandable microspheres that have not been surface-modified has too few coating layer particles loaded on them, and after subsequent processing, too little 3-phenylsulfonylbenzenesulfonic acid flame retardant is retained, resulting in a significant decrease in the flame retardant effect.
[0079] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0080] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing environmentally friendly flame-retardant pearl cotton, characterized in that: The steps include: Step 1: Add carbon nanotubes, carbon fibers and dimethylformamide into a reactor, perform ultrasonic dispersion for 3-4 hours, then add EVA elastomer and maleic anhydride grafted polyethylene compatibilizer into the reactor, stir at 50-60°C and 300-500r / min for 1.5-2 hours, concentrate under reduced pressure, vacuum dry the remaining solid, crush and pelletize to obtain antistatic masterbatch; Step 2: Add 3-phenylsulfonylbenzenesulfonic acid flame retardant powder and deionized water into a reaction kettle, stir at 20-25°C and 200-300r / min for 10-15min, then add composite heat-expandable microspheres, ultrasonically disperse for 8-12h, filter, wash the filter cake with deionized water 2-3 times, and vacuum dry at 45-50°C to obtain flame-retardant heat-expandable microspheres; Step 3: Add low-density polyethylene resin, antistatic masterbatch, antioxidant and stearic acid into a high-speed mixer and mix evenly, then add flame-retardant heat-expandable microspheres and mix evenly again to obtain a mixture, transfer the mixture to an extrusion foaming machine for extrusion foaming, the extrusion temperature is 130-140°C, the foaming temperature is 175-190°C, the foaming time is 6-7min, naturally cool, cut and shape, and obtain environmentally friendly flame-retardant pearl cotton; The mass ratio of the low-density polyethylene resin, the antistatic masterbatch, the antioxidant, the stearic acid and the flame-retardant thermal expansion microspheres is 80-85:20-22:1:1:6.5-7.
2. The method for preparing an environmentally friendly flame-retardant pearl cotton according to claim 1, characterized in that: The usage ratio of the carbon nanotubes, carbon fibers, dimethylformamide, EVA elastomer and maleic anhydride grafted polyethylene compatibilizer in step 1 is 2-3:4-6:1000-1500:50-80:50-60.
3. The method for preparing an environmentally friendly flame-retardant pearl cotton according to claim 1, characterized in that: The mass ratio of the 3-phenylsulfonylbenzenesulfonic acid flame retardant powder, deionized water and composite thermal expansion microspheres in step 2 is 1:100:2-2.
5.
4. The method for preparing an environmentally friendly flame-retardant pearl cotton according to claim 1, characterized in that: The composite heat-expandable microspheres are prepared by the following steps: Aluminum nitrate nonahydrate and anhydrous ethanol are added to a reaction kettle, stirred at 20-25° C. and 200-300 r / min for 10-15 min, then the modified heat-expandable microspheres are added, ultrasonically dispersed for 10-15 min, and then a 1.75wt% ethanol solution of 2-methylimidazole is added, and the mixture is stirred for 60-80 min, allowed to stand at 35° C. for 24 h, and centrifuged and filtered, and the filter cake is washed with anhydrous ethanol for 2-3 times, and vacuum dried at 45-50° C. to obtain composite heat-expandable microspheres; The dosage ratio of the aluminum nitrate nonahydrate, anhydrous ethanol, modified heat-expandable microspheres and the methanol solution of 2-methylimidazole is 0.25-0.3 g: 30 mL: 0.1-0.12 g: 30 mL.
5. The method for preparing an environmentally friendly flame-retardant pearl cotton according to claim 4, characterized in that: The modified heat-expandable microspheres are prepared by the following steps: Heat-expandable microspheres and 1 mol / L hydroxylamine aqueous solution are added into a reaction kettle at a mass ratio of 1:400-500, stirred at 60-70°C and 200-300 r / min for 10-15 min, filtered, the filter cake is washed with deionized water for 2-3 times, and vacuum dried at 45-50°C to obtain modified heat-expandable microspheres.
6. The method for preparing an environmentally friendly flame-retardant pearl cotton according to claim 5, characterized in that: The heat-expandable microspheres are prepared by the following steps: Magnesium chloride hexahydrate, sodium dodecyl sulfate and deionized water are added to a reaction kettle, stirred at a speed of 800-1000 r / min for 20-30 min, and then sodium nitrite and polyvinyl pyrrolidone are added to the reaction kettle, and ultrasonic dispersion is performed for 15-20 min to obtain a water phase; ethylene glycol dimethacrylate, azobisisobutyronitrile and a foaming agent are dissolved in a polymerizable monomer to obtain an oil phase, which is stored at 0-4°C; The aqueous phase is added to a homogenizer, and the oil phase is added to the homogenizer under stirring conditions of 8000-10000 r / min. After stirring for 2-3 minutes, the mixture is transferred to a reactor, and the temperature is raised to 60°C under nitrogen protection and 300-500 r / min. The mixture is kept warm for reaction for 20-24 hours, and allowed to stand at 70°C for 20-30 minutes. The pH value is adjusted to 2 with 0.1 mol / L hydrochloric acid, and the mixture is filtered. The filter cake is washed with deionized water until the last washing liquid is neutral, and then dried under vacuum at 45-50°C to obtain heat-expandable microspheres. The mass ratio of the water phase to the oil phase is 1.2:
1.
7. The method for preparing an environmentally friendly flame-retardant pearl cotton according to claim 6, characterized in that: The mass ratio of magnesium chloride hexahydrate, sodium dodecyl sulfate, deionized water, sodium nitrite and polyvinyl pyrrolidone is 10-12: 1-1.5: 95-105: 0.02-0.03: 0.02-0.03; the mass ratio of ethylene glycol dimethacrylate, azobisisobutyronitrile, foaming agent and polymerizable monomer is 0.24-0.26: 1.2-1.5: 24-26: 95-100.
8. The method for preparing an environmentally friendly flame-retardant pearl cotton according to claim 7, characterized in that: The foaming agent is any one of isobutane, n-pentane and isopentane; the polymerizable monomer is prepared by mixing methyl methacrylate, N,N-dimethylacrylamide and vinyl acetate in a mass ratio of 7:3:
1.
9. The method for preparing an environmentally friendly flame-retardant pearl cotton according to claim 1, characterized in that: The 3-phenylsulfonylbenzenesulfonic acid flame retardant powder is prepared by the following steps: Potassium 3-phenylsulfonylbenzenesulfonate and a hydrochloric acid solution with a concentration of 0.1 mol / L are added into a reaction kettle in a mass ratio of 1:20-25, stirred for 10-12 hours under the conditions of ultrasonic assistance, 30-35° C. and 500-800 r / min, and centrifuged and washed 3-5 times to obtain 3-phenylsulfonylbenzenesulfonic acid flame retardant powder; The power of the ultrasonic assistance is 450-500W, and the frequency is 30-40KHz.
10. An environmentally friendly flame-retardant pearl cotton and a preparation method thereof, characterized in that: The invention is prepared by the preparation method of the environmentally friendly flame-retardant pearl cotton described in any one of claims 1 to 9.
Citation Information
Cited By
Long-acting flame-retardant aluminized air bubble film as well as preparation method and application thereof
CN120396478A
Flame-retardant anti-static composite pearl wool material and preparation method thereof
CN121021957A